ACCESSIBILITY ANALYSIS, ACCESS AND CERTIFICATIONS OF INFORMATION FROM A VIRTUAL HEALTH FORUM - Michel Marcosi Cintra; Naira Favoretto; Alef Janguas; Filipe Lopes; Christoph Kaeppler; Fabiana Faleiros (Associação Portuguesa dos Enfermeiros de Reabilitação, 2019)
Introduction: Spina Bifida (EB) is the most frequent congenital malformation in the world, responsible for important neurological sequelae, compatible with life. Given this, it is necessary to identify and develop educational technologies, which help in the training and support to individuals with EB and their families. In this direction, a virtual forum was developed for individuals with EB and their relatives, MieloFórum. Objective: The purpose of this study is to evaluate the accesses, the accessibility of its users and to guarantee a quality certification to the same. Method: For the analysis of HTML errors, the access errors of MieloFórum were collected, the accesses analyzed and submitted to a quality certification. Results and Discussions: the forum was developed and evaluated, and a total of 28 problems were found in the forum code, taking into account the new rules of standardization of the World Wide Web Consortium, it was comprehensive in accesses in the analyzed period and submitted to quality certification . There were more than 1500 accesses in 7 months with a demand in several countries. Conclusion: MieloForum's submission to an accessibility analysis tool proved to be useful for judging and correcting identified problems, enhancing it together with quality certification.